The roles of Islamic NGO in dealing with Feminism agenda in Malaysia: Peranan NGO Islam dalam menangani agenda Feminisme di Malaysia - Mohd. Salleh, Norsaleha (al-Irsyad: Journal of Islamic and Contemporary Issues, 2016)
The study aims to survey the roles of Wanita Ikatan Muslimin Malaysia (Women of the Muslim Association of Malaysia), an Islamic NGO whose efforts are directly involved in the repudiation of the feminist agenda in Malaysia. The feminism movement is among the agendas of the enemies of Islam and aims to mutilate Muslim women’s personalities and identities. It comes in the form of an intellectual invasion, a call for freedom, gender equality, and humanity. Such slogans successfully created deception and delusion in the eyes of Muslim women, like an oasis in the desert, until they were viewed as genuine and evident. The study used an action research approach by employing the Kemmis and McTaggart Action Research Model. It was conducted based on four action steps: reflecting, planning, taking action, and observing. The study outcomes showed that the repudiation was shown through the Save the Ummah Campaign (SUC), the Reject Comango Campaign, the Women: Your Honour is Because of Islam Campaign, the Women Gathering, Women Fiqh, and through seminars and conventions conducted from time to time. The repudiation efforts were also highlighted by writing books and counter-statements towards feminist groups via ISMA Women’s website, Facebook page, ISMAweb media, and other liberal media such as MalaysiaKini, Malaysia Insider, and so on. These efforts were made to provide awareness among the Muslim community in Malaysia so that they are more sensitive to coming together to defend the identity and personality of Muslim women from being influenced by the agenda of feminist groups.